The Effect of the Realistic Mathematics Education (RME) Approach Assisted by Augmented Reality (AR) on Improving Grade V Students' Numeracy Skills at SDN Pegambiran 1 - Nurjanah, Rahma Maulinda; Asyiah, Nur; Sutisno, Aliet Noorhayati (Jurnal Ragam Pengabdian, 2026)
Based on the Rapor Pendidikan (Education Report Card), the numeracy skills of Grade V students at SD Negeri Pegambiran I remain below the expected minimum competency level. This study aimed to examine the effect of the Realistic Mathematics Education (RME) approach assisted by Augmented Reality (AR) on improving students' numeracy skills. A quantitative pre-experimental method with a one-group pretest-posttest design was employed. The population consisted of 27 students, while 25 Grade V students were selected using saturated sampling. Data were collected through numeracy tests and observation sheets and analyzed using normality, paired t-test, and N-Gain analyses. The findings showed that the data were normally distributed. The paired t-test revealed a significant improvement in numeracy skills (t = 26.724; p < 0.001), indicating that the RME approach assisted by AR had a significant positive effect. The N-Gain score of 0.607 (60.70%) indicated a moderate level of improvement. It can be concluded that integrating the RME approach with AR effectively enhances elementary students' numeracy skills in learning the area of two-dimensional shapes. The novelty of this study lies in combining contextual mathematics learning through RME with interactive AR technology to strengthen elementary students' numeracy competencies.